Gender-Responsive Researchers Equipped for Agricultural Transformation (GREAT): Trainer’s Manual for the Gender-Responsive Plant Breeding Course (Level 2) - Mangheni, M.N.; Tufan, H.A.; Asiimwe, E. (CAB International, 2024)
This manual presents the training process for the Gender-Responsive Plant Breeding course, implemented by Makerere and Cornell Universities, over a period of five years (2016-2020), under the Gender-Responsive Researchers Equipped for Agricultural Transformation (GREAT) project funded by the Bill and Melinda Gates Foundation. It has five broad parts: I) Introduction; II) Required preparation before the course; III) Phase one (9-day, face-to-face training); IV) the 5-month Field Training phase; and V) Phase two (5-day, face-to-face training). Each session consists of specific learning objectives, session plans and slides, delivery methods, practical exercises and examples, as well as relevant tips and synthesized take-home messages. The sessions were developed by an international multidisciplinary team of experts in gender and agriculture and subjected to a rigorous peer review and quality assurance process. GREAT aims to contribute to building a pool of gender-responsive agricultural researchers able to advance more equitable and effective agricultural systems in Africa and beyond. This manual is for all facilitators/trainers interested in applied, gender responsive agricultural research.